Art with a message protest and propaganda, satire and social comment. (Mount Kisko, N.Y. Center for Humanities, 1971)
How art has been used as a vehicle for propaganda and protest.
VHS format.
Keywords: World politics -- Caricatures and cartoons; Politics and art; Art and society